Floristic relationship between scrubland and grassland patches in the Mediterranean landscape of the Iberian Peninsula (Plant Ecology, 2000)
In the rural Mediterranean landscape, mosaics of patches of sclerophyllous scrubland and semi-natural grasslands are frequent. The plant communities of these patches, which are physiognomically easy to recognise, are very heterogeneous. The objective of this paper is to determine whether the patches of scrub-grassland represent an integrated response unit of the vegetation with regard to the physical environment (climatic, geographical and edaphic factors) and human use, or whether, on the contrary, this is an independent response. In order to do this a total of 50 sampling sites where scrubland and grassland patches were in contact were studied along a 370 km E-W mesoclimatic gradient from central Spain to Portugal (Iberian Peninsula). Two distinct zones, the east and the west halves of the study area, were identiﬁed according to the plant communities. Within each of these zones, each type of patch responded to the previously mentioned factors, differentially and independently. This determined a general lack of inter-community association or ﬂoristic correlation between scrub and grassland plant communities in contact. The spatial association is a random process probably related to the particular human management realised on every scrubland and grassland patch. The scrub–grassland pattern, which is characteristic of the Mediterranean landscape, does not represent an integrated response unit of the vegetation to a given environment, but rather the sum of the independent responses to the environment of the two patches in contact.